2020
DOI: 10.1111/joes.12389
|View full text |Cite
|
Sign up to set email alerts
|

How to Make a Pie: Reproducible Research for Empirical Economics and Econometrics

Abstract: Empirical economics and econometrics (EEE) research now relies primarily on the application of code to datasets. Handling the workflow linking datasets, programs, results and finally manuscript(s) is essential if one wish to reproduce results, which is now increasingly required by journals and institutions. We underline here the importance of "reproducible research" in EEE and suggest three simple principles to follow. We illustrate these principles with good habits and tools, with particular focus on their im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 96 publications
(168 reference statements)
0
8
0
Order By: Relevance
“…However, despite an apparent consensus on the general problem, the publication of papers exhorting the scientific community to publish reproducible results, and the dissemination of tools, good practices and courses (Stodden et al, 2013;Gentzkow and Shapiro, 2013;Sandve et al, 2013;Orozco et al, Forthcoming 2021), we still observe considerable weaknesses in both researcher and journal practices, leading to the scarce dissemination of raw scientific materials. 1 Many journals do not have a replication or data and code availability policy.…”
Section: The Need For Reproducible Researchmentioning
confidence: 92%
See 3 more Smart Citations
“…However, despite an apparent consensus on the general problem, the publication of papers exhorting the scientific community to publish reproducible results, and the dissemination of tools, good practices and courses (Stodden et al, 2013;Gentzkow and Shapiro, 2013;Sandve et al, 2013;Orozco et al, Forthcoming 2021), we still observe considerable weaknesses in both researcher and journal practices, leading to the scarce dissemination of raw scientific materials. 1 Many journals do not have a replication or data and code availability policy.…”
Section: The Need For Reproducible Researchmentioning
confidence: 92%
“…Others (Baiocchi, 2007;Orozco et al, Forthcoming 2021) have identified possible organizational improvements at the researcher level. These authors proposed principles to link a paper to its raw components, data and code through a clear workflow, following the original idea of reproducible research documents proposed by Knuth (1984Knuth ( , 1992 and his literate programming approach.…”
Section: F I G U R E 1 Pictograms Of Inputs and Outputs Of Empirical Research (Simplified)mentioning
confidence: 99%
See 2 more Smart Citations
“…The benefits of computational reproducibility-and increased access to data and code, more generally-have already been articulated many times by researchers in many different fields: archaeology (Marwick 2017), bioinformatics (Mangul et al 2018), cell biology (Grüning et al 2018), computational fluid mechanics (Mesnard and Barba 2017), computer systems research (Collberg and Proebsting 2016), economics (Anderson et al 2008;Koenker and Zeileis 2009;Orozco et al 2018), epidemiology (Coughlin 2017;Peng, Dominici, and Zeger 2006;Shepherd et al 2017), geosciences (Claerbout and Karrenbach 1992;Gil et al 2016;Konkol et al 2019), high-energy physics (Chen et al 2018), hydrology (Hutton et al 2016), mathematical and computational biology (Schnell 2018), machine learning (Hutson 2018;Tatman et al 2018), neuroscience (Crook, Davison, and Figure 1. Fragile Families Challenge data structure.…”
Section: Computational Reproducibilitymentioning
confidence: 99%